Survey of Financial Literacy of Bank Customers on the Use of Electronic Banking and Reducing of Traffic Accidents - Mohsen Ghane; Nasim Shahmoradi; Mahmoud Moein (Shahid Sadoughi University of Medical Sciences, 2019)
Introduction: One of the factors affecting the health of the society is economic factors, and financial literacy and familiarity in the field of electronic banking can affect the economics of individuals. The purpose of this study was to investigate the effect of financial literacy of bank customers on the use of electronic banking and the reduction of traffic accidents. Methods: This descriptive study was conducted in a researcher-made questionnaire using Cronbach's alpha = 0.87. The research community was Yazd banks' customers in 2017. The research sample was determined and 380 people were randomly selected. Data analysis was performed using structural equation modeling (SEM) with partial least squares (PLS) approach. Results: Data analysis showed that 73% of the samples was male and 38% of them were between the ages of 30-39 and 41% had a bachelor's degree. The value of the path coefficient (beta) of the customers' financial literacy to the use of electronic banking is equal to (0.493). Conclusion: The results indicated a positive and significant impact of financial literacy and its domains on the use of electronic banking, which can indirectly reduce traffic and road accidents.